Corporate Governance Mechanisms and Their Impact on Earnings Management Practices - Anizul Mufidatun Nisa'; Arum Pujiastuti (Universitas Negeri Surabaya, 2025)
This study examines the impact of managerial ownership, institutional ownership, board size, audit quality, and independent commissioners on earnings management in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018–2022. The research uses secondary data from 28 companies selected through purposive sampling, resulting in 140 observations over five years. A panel data regression analysis was conducted using the Fixed Effect Model (FEM) as the best-fit model based on Chow and Hausman tests. The results show that, simultaneously, the independent variables have a significant effect on earnings management. Partially, only institutional ownership has a significant negative influence, indicating its effectiveness in monitoring management to reduce earnings manipulation. The remaining variables—managerial ownership, board size, audit quality, and independent commissioners—do not show significant effects. The study highlights the importance of institutional investors and strong corporate governance mechanisms in improving financial transparency and reducing earnings management